E, Ernani PRINSIP KESOPANAN TUTURAN GADIS DESA DALAM CERITA RAKYAT OGAN KOMERING ILIR: KAJIAN PRAGMATIK - ernani, ernani ernani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2023)
This study aims to describe the politeness principle of village girl speech in the folklore of Ogan Komering Ilir. The method used is descriptive qualitative method. In this study using Leech's theory of politeness principles and using a pragmatic approach. The data source is in the form of the folklore of Putri Jari Sakti and the Princess with Golden Hair. The results of the study show that there are dominant and less dominant maxims between the two folklores, namely 4 utterances which include the maxim of sympathy in the folklore of Putri Berambut Emas and 3 utterances respectively which include the maxim of keeping feelings and the maxim of agreement in the folklore of Putri Jari Sakti. On the other hand, the total maxim that is most dominant in these two folktales is the maxim of sympathy, namely 5 utterances. Meanwhile, the total number of maxims is the least, namely the maxims of giving approval for only 2 utterances.